Student and teacher perceptions of plagiarism in academic writing - Bacha, Nahla Nola (2010)
Writing is no easy task in any discipline and at any stage in a student’s course of university study. In addition, it brings with it the important concern of plagiarism. Obtaining student and teacher perceptions of the strategies students use to produce their assignments has been valuable in identifying and dealing with plagiarism. This article reports on a survey carried out at one English-medium university in Lebanon of 358 Arabic student views by discipline and year and 31 teacher views on the strategies students use to “improve” their written assignments. Results show that although students are aware of the prevalence of plagiarism in all disciplines and in all years of study, they perceive more incidences in the professional disciplines, at advanced levels, and in student use of strategies that give help to and gain help from their peers. Teachers indicated higher student use of all strategies and a greater extent of plagiarism than did the students. Recommendations in line with recent research emphasizing more positive methods are made for raising student awareness of ethical writing strategies, establishing common ground on what constitutes plagiarism, and implementing pedagogical practices and institutional policies that educate rather than penalize.